PERAN CITRA SATELIT LANSAT 8 OLI/TIRS UNTUK ANALISIS DAERAH RESAPAN AIR DI KABUPATEN MAGELANG, JAWA TENGAH - Anggoro, Hengky; Winarti, Winarti (KURVATEK, 2025)
This study aims to analyze the distribution of groundwater recharge potential areas in Magelang Regency using a Geographic Information System (GIS) approach and Landsat 8 OLI satellite imagery. The analysis was conducted by integrating four key parameters: land cover, soil type, slope gradient, and rainfall, utilizing a scoring and overlay method. Supporting data such as the National Digital Elevation Model (DEMNAS) were used for topographic analysis. Rainfall data were obtained from CHIRPS, while soil type maps were sourced from FAO/UNESCO to support spatial modeling. The results revealed that approximately 27% of the Magelang Regency area has high groundwater recharge potential, 59% falls into the moderate (natural) category, and 14% is classified as critical to highly critical. Areas with high recharge potential are generally characterized by dense vegetation cover, highly porous soils, and relatively gentle to moderate slopes. In contrast, areas with low recharge potential are commonly found in built-up regions and steep slopes that are prone to surface runoff. These findings are expected to provide valuable insights for groundwater conservation planning and sustainable land use management. The implementation of integrated conservation strategies is crucial to enhance soil infiltration capacity and maintain the hydrological cycle balance in Magelang Regency